Targeting lactylation and the STAT3/CCL2 axis to overcome immunotherapy resistance in pancreatic ductal adenocarcinoma - Chen, Qun; Yuan, Hao; Bronze, Michael S.; Li, Min (The Journal of Clinical Investigation, 2025)
Metabolic reprogramming in pancreatic ductal adenocarcinoma (PDAC) fosters an immunosuppressive tumor microenvironment (TME) characterized by elevated lactate levels, which contribute to immune evasion and therapeutic resistance. In this issue of the JCI, Sun, Zhang, and colleagues identified nonhistone ENSA-K63 lactylation as a critical regulator that inactivates PP2A, activates STAT3/CCL2 signaling, recruits tumor-associated macrophages (TAMs), and suppresses cytotoxic T cell activity. Targeting ENSA-K63 lactylation or CCL2/CCR2 signaling reprograms the TME and enhances the efficacy of immune checkpoint blockade (ICB) in PDAC preclinical models. This work provides critical insights into the metabolic-immune crosstalk in PDAC and highlights promising therapeutic strategies for overcoming immune resistance and improving patient outcomes.